2020
DOI: 10.1177/2150132720984416
|View full text |Cite
|
Sign up to set email alerts
|

Tennessee Healthcare Provider Practices, Attitudes, and Knowledge Around HIV Pre-Exposure Prophylaxis

Abstract: Introduction/Objectives: Pre-exposure prophylaxis (PrEP) use in the southern United States is low despite its effectiveness in preventing HIV acquisition and high regional HIV prevalence. Our objectives were to assess PrEP knowledge, attitudes, and prescribing practices among Tennessee primary care providers. Methods: We developed an anonymous cross-sectional electronic survey from March to November 2019. Survey development was guided by the Capability, Opportunity, Motivation, and Behavior framework and refin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…of IRS is an important step in recommending its use. It is equally important to enhance the capacity of healthcare providers 39,40. …”
mentioning
confidence: 99%
“…of IRS is an important step in recommending its use. It is equally important to enhance the capacity of healthcare providers 39,40. …”
mentioning
confidence: 99%
“…A previous study found that patient request for PrEP was significantly associated with prescriptions; therefore, efforts should also focus on patient education about PrEP. 11 Additionally, providers felt more comfortable discussing sexual history with patient populations such as MSM but felt the least comfortable with transgender populations. 11 Educating providers on how to navigate conversations about sexual practices and PrEP with all patients may be an important step for increasing PrEP use.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additionally, providers felt more comfortable discussing sexual history with patient populations such as MSM but felt the least comfortable with transgender populations. 11 Educating providers on how to navigate conversations about sexual practices and PrEP with all patients may be an important step for increasing PrEP use. For this BPA to accurately flag a patient as meeting criteria for PrEP use, sexual orientation and gender identity needed to be documented in the chart.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 For instance, in a sample of Minnesota physicians, 58.1% felt that cannabis was a legitimate medical treatment but 50.0% did not feel ready or did not want to answer patient questions about cannabis. 10 Moore et al 11 found that a majority of clinicians felt they were obligated to provide information and to prescribe HIV PrEP, as well as to refer a patient if they could not prescribe, despite low rates of prescribing. Authors have found that clinicians who have prescribed PrEP are more comfortable taking a sexual history, more knowledgeable about PrEP, and more likely to have had a patient request it.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Prior studies also looked at these factors in relation to advance care planning and hospice referrals 9 as well as other potentially controversial topics such as cannabis use 10 and HIV preexposure prophylaxis (PrEP). [11][12][13][14] Finally, it is important to understand to what extent existing concerns about physician participation in MAID-such as inaccuracy of prognostication, conflict with professional norms and roles, and potential worsening of preexisting social and cultural biases against older adults and individuals with terminal illness-apply to APP participation. 15,16 Although the American Medical Association now includes ethical arguments both for and against MAID, its formal stance remains one of opposition to physician participation.…”
Section: Introductionmentioning
confidence: 99%